Research progress of restraining campus bullying by martial arts training (Revista de Artes Marciales Asiáticas, 2019)
This narrative review analyzed the existing research related to the practice of martial arts and campus bullying. This literature suggests that martial arts training can reduce bullying behaviors by improving individual self-control and self-esteem, reducing hostility and strengthening interpersonal communicative ability. Current research also emphasizes the efficacy of those martial arts activities that pay attention to participants’ moral education or norms of proper social behavior in order to improve physical cognition and lead to restraining individual bullying behavior. Future research should focus on cross-cultural factors and local situations, combine quantitative and qualitative research methods, and explore the internal mechanism of martial arts training to curb campus bullying, so as to explore new ways in which martial activity can promote individual psychological adjustment and to positively address problem behavior.